Molecular phylogenetic status of the Bulgarian marbled polecat (Vormela peregusna, Mustelidae, Carnivora), revealed by Y chromosomal genes and mitochondrial DNA sequences. (February 2017) - Mizumachi, Kaito; Nishita, Yoshinori; Spassov, Nikolai; Raichev, Evgeniy G.; Peeva, Stanislava; Kaneko, Yayoi; Masuda, Ryuichi
Abstract: In this study, we investigated molecular phylogenetic status of the marbled polecat ( Vormela peregusna ) from Bulgaria, using sequences of two Y-chromosomal genes ( SRY and ZFY ). The phylogenetic tree inferred using combined sequences of both genes indicated that the marbled polecat was split from genera Lutra, Neovison and Mustela after genus Martes was diverged in family Mustelidae. In addition, we analyzed molecular phylogeography of the Bulgarian population of the marbled polecat, using cytochrome b and control region sequences of mitochondrial DNA (mtDNA). The phylogenetic tree of cytochrome b indicated that the haplotypes of the Bulgarian population comprised two haplogroups, which were the most ancestral clades. Additionally, the control region phylogeny showed that the haplotypes of Bulgaria formed two haplogroups: one was the most ancestral clade, and the other was the derivative clade. One individual with the most ancestral cytochrome b clade had a control region haplotype of the derivative clade. Thus, this study revealed that the most ancestral lineages of the marbled polecat are included in the population of Bulgaria. The Bulgarian population could be a remnant lineage from a basal for the species, which in Pleistocene occupied a relatively large area related to the Balkan-Caucasian. Highlights: Molecular phylogeny of the marbled polecat using two Y chromosomal genes. Phylogeography of the Bulgarian marbled polecats using mitochondrial DNA. The Bulgarian marbled polecat could be the most ancestral lineages of the species.